2003
DOI: 10.1095/biolreprod.102.005793
|View full text |Cite
|
Sign up to set email alerts
|

Is the Cadherin/Catenin Complex a Functional Unit of Cell-Cell Actin-Based Adherens Junctions in the Rat Testis?1

Abstract: Much controversy exists regarding the presence of the cadherin/catenin complex and its intracellular attachment site in the testis, which is the functional unit for actin-based cell-cell adherens junctions (AJs) in multiple epithelia. Furthermore, whether germ and Sertoli cells are equipped with the necessary AJ-associated signaling molecules to regulate this cadherin/catenin complex during spermatogenesis is not known. In the present study, it was shown that both Sertoli and germ cells indeed express N-cadher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
176
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 153 publications
(198 citation statements)
references
References 112 publications
(165 reference statements)
22
176
0
Order By: Relevance
“…The effects of adjudin on Sertoli-germ cell adhesion have been well documented in both in vitro and in vivo studies Grima et al, 2001;Chen et al, 2003b;Lau and Mruk, 2003;Lee et al, 2003;Lui et al, 2003;Siu et al, 2003;Mruk et al, 2006;Wolski et al, 2006) (Table 1), and these reports have shown that adjudin exerts its effects on Sertoli-germ cell adhesion by activating two separate but related signaling cascades. It was found that integrin and RhoB were activated within hours of adjudin treatment (Lui et al, 2003;Siu et al, 2003).…”
Section: E Mechanism Of Adjudin Action In the Testis: The Current Modelmentioning
confidence: 95%
See 4 more Smart Citations
“…The effects of adjudin on Sertoli-germ cell adhesion have been well documented in both in vitro and in vivo studies Grima et al, 2001;Chen et al, 2003b;Lau and Mruk, 2003;Lee et al, 2003;Lui et al, 2003;Siu et al, 2003;Mruk et al, 2006;Wolski et al, 2006) (Table 1), and these reports have shown that adjudin exerts its effects on Sertoli-germ cell adhesion by activating two separate but related signaling cascades. It was found that integrin and RhoB were activated within hours of adjudin treatment (Lui et al, 2003;Siu et al, 2003).…”
Section: E Mechanism Of Adjudin Action In the Testis: The Current Modelmentioning
confidence: 95%
“…In the testis, Sertoli and germ cells have been shown to express both E-and N-cadherin (Wu et al, 1993;Lee et al, 2003), but the expression of E-cadherin by germ cells was considerably higher than that of N-cadherin . In addition, E-cadherin expression in undifferentiated type A spermatogonia was recently demonstrated in the mouse testis (Tokuda et al, 2007), which clearly illustrates that spermatogonia use this cell adhesion protein predominantly to adhere to Sertoli cells.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%
See 3 more Smart Citations